How to be SMART in oncology: A practical framework to assess the contribution of phase using sequential multiple adaptive randomized treatment designs - Kristine R. Broglio; Elizabeth F. Krakow; Erica E. M. Moodie (Clinical Trials, 2026)
Background: Sequential multiple adaptive randomized treatment designs can generate registrational-quality evidence for the contribution of phase in perioperative oncology by preserving randomized comparisons and intent-to-treat estimation while improving efficiency relative to traditional three-arm trials, and yet they remain underappreciated. We present a sequential multiple adaptive randomized treatment design framework for perioperative regimens with neoadjuvant and adjuvant phases, motivated by perioperative immunotherapy in resectable non-small-cell lung cancer, where the benefit of neoadjuvant therapy is hypothesized to be greater than that of adjuvant therapy. Methods: We define analyses for perioperative-versus-control, neoadjuvant-only-versus-control, and contribution of phase (incremental adjuvant benefit). We specify intent-to-treat analysis sets and describe unbiased estimation. Results: In a hypothetical trial calibrated to a perioperative setting, a sequential multiple adaptive randomized treatment design increases the number of events for regimen-versus-control comparisons and isolates a randomized comparison for the contribution of phase at the second randomization. Compared with a traditional multi-arm design, simulations demonstrate controlled family-wise type I error (